Career planning in Bangladesh Civil Service (Administration) Cadre: a critical assessment - Chakraborty, Devabrata (BRAC University, 2010)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Governance and Development, 2008.